Laparoscopic Versus Open Appendicectomy: A Comparison of Primary Outcome (Faridpur Medical College Journal, 2015)
Currently, laparoscopic appendectomy is widely practiced for the management of acute appendicitis. It is not clear whether open or laparoscopic appendectomy is more appropriate. Our aim was to compare the safety and the advantages of laparoscopic versus open appendectomy in a prospective study. 102 patients were participated in this study. The group 1 patients were subjected to laparoscopic appendectomy [LA], whereas the group 2 patients were subjected to open appendectomy [OA]. 46 patients included in LA group and 54 patients in OA group. The mean operative time for LA and OA was 84.4 (45-220) minutes and 59 (30-180) minutes respectively. Although LA was associated with a shorter hospital stay [LA-3.5 days versus OA-5 days] but duration of operation is prolong in LA than OA and the postoperative wound infection is significantly higher in OA than LA. LA is safe and superior to OA in respect to an early discharge, lesser postoperative pain; decreased post operative wound infection, early return to work and a better cosmetic scar.Faridpur Med. Coll. J. 2014;9(2): 84-87